Design and Control Development of an Autonomous Visitor Guiding Robot in a Hospital Environment - Agus Siswoyo; Pippie Arbiyanti; Rodik Wahyu Indrawan (Jurnal Teknologi, 2023)
Mobile robot technology, coupled with artificial intelligence, has reached a point where robots can now autonomously navigate and store area data, while the integration of smart sensor and controller technology enables them to detect and adapt to dynamic environments by making predictions under diverse conditions. In general, hospital visitors do not have sufficient preparation and knowledge accompanied by sudden situations, this often makes visitors, namely patients and patient companions confused and panicked. The reality is that until now, many visitors are still pacing in the wrong room, asking the officers many times, which eventually leads to misunderstandings by visitors to the hospital system, facilities, and services which are considered complicated and make visitors dissatisfied. Applied technology innovation Design and control of autonomous visitor guide robots in hospital environments (Viguro Robot) offers solutions using interactive robots that can provide location information and deliver visitors to their intended location. Artificial intelligence is employed through the utilization of sensors, digital data, or remote input, allowing the amalgamation of hospital patient data, instant material analysis, and the utilization of insights derived from Viguro Robots' sensors. This robot is designed by utilizing the development of autonomous mobile robot technology, interactive human machine interface, localization and mapping, and obstacle avoidance. The stages in making the robot begin with design planning, initial testing, stage I validation, stage II validation, and implementation testing. This applied innovation of technology is expected to offer solutions in order to improve facilities and quality of service to patients and patient companions in hospitals.